2002
DOI: 10.1161/01.res.0000029085.69891.f2
|View full text |Cite
|
Sign up to set email alerts
|

Sarcolemmal K ATP Channel Triggers Opioid-Induced Delayed Cardioprotection in the Rat

Abstract: Recently, the involvement of sarcolemmal K ATP (sarcK ATP ) channels in ischemic and pharmacological preconditioning (IPC and PPC) has been minimized by numerous studies suggesting a primary role for mitochondrial K ATP (mitoK ATP ) channels in early and delayed cardioprotection. Although the mitoK ATP channel has clearly been shown to be a distal effector of delayed IPC and PPC, studies implicating it as a trigger of protection in delayed IPC are lacking. Accordingly, we characterized the role of cardiac K AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 27 publications
2
35
1
Order By: Relevance
“…Furthermore, opioids have primarily been used for immediate protection. Only one group has previously shown a delayed protection by this stimulus, which was in rats (Patel et al 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, opioids have primarily been used for immediate protection. Only one group has previously shown a delayed protection by this stimulus, which was in rats (Patel et al 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Morphine has been reported to protect against ischemiareperfusion injury and reduce myocardial infarct size in rats (Patel et al, 2002), as well as rabbits (Miki et al, 1998), and protect the cardiomyocytes in the chicken embryo (Liang and Gross, 1999). It has been further demonstrated that the ␦-receptor agonist DADLE and the -receptor agonist U-50488H could reduce myocardial infarct size and the incidence of arrhythmia in a cardiac ischemia-reperfusion model of the rat (Valtchanova-Matchouganska and Ojewole, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of opioid receptors has been shown to be cardioprotective by mimicking the effects of ischemic preconditioning in several experimental settings (Liang and Gross, 1999;Miki et al, 1998;Patel et al, 2002). In isolated rabbit hearts perfused on a Langendorff apparatus, morphine mimicked the effect of ischemic preconditioning in protecting the heart from being injured (Miki et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also noteworthy that in nonpreconditioned hearts from both male (21,27) and female (2) rats, it has been demonstrated that the putative mitochondrial K ATP channel antagonist 5-hydroxydecanoate (5-HD) has no effect on infarct size, suggesting that mitochondrial K ATP channels do not play a central role in the sexdependent differences in the susceptibility of the heart to myocardial infarction. This also indicates that the intrinsic, sex-dependent resistance of the heart to I/R injury is not analogous to a broad array of acquired cardioprotection models, almost all of which have been shown to be 5-HD sensitive (5,8,9,14,(21)(22)(23). One notable exception is cardioprotection acquired by long-term exercise, which has recently been shown to be HMR-1098 sensitive and 5-HD insensitive (2); interestingly, this study was conducted on female rats.…”
Section: Discussionmentioning
confidence: 99%